2007
DOI: 10.1179/136485907x176319
|View full text |Cite
|
Sign up to set email alerts
|

The ticks (Acari: Ixodida: Argasidae, Ixodidae) of Paraguay

Abstract: The ticks reported in Paraguay, which are here reviewed, can be categorized as 'endemic or established' (Argas persicus or a sibling species, Ornithodoros hasei, O. rostratus, O. rudis, O. talaje/O. puertoricensis, Amblyomma aureolatum, Am. auricularium, Am. brasiliense, Am. cajennense, Am. calcaratum, Am. coelebs, Am. dissimile, Am. dubitatum, Am. incisum, Am. longirostre, Am. nodosum, Am. ovale, Am. pacae, Am. parvum, Am. pseudoconcolor, Am. rotundatum, Am. scutatum, Am. tigrinum, Am. triste, Dermacentor nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 27 publications
0
19
0
3
Order By: Relevance
“…Guglielmone et al (2003) note specimen records of Amblyomma auricularium, though this species is more often associated with armadillos of the genus Dasypus. Nava et al (2007) note the presence of the Ixodid tick Amblyomma calcaratum in Paraguay, though the collectors did not note the host species. Botelho et al (1989) report Amblyomma pseudoconcolor, A.calcaratum and A.maculatum from this species in Minas Gerais, Brazil.…”
Section: (En Linea Directa News Report April 2007)mentioning
confidence: 99%
“…Guglielmone et al (2003) note specimen records of Amblyomma auricularium, though this species is more often associated with armadillos of the genus Dasypus. Nava et al (2007) note the presence of the Ixodid tick Amblyomma calcaratum in Paraguay, though the collectors did not note the host species. Botelho et al (1989) report Amblyomma pseudoconcolor, A.calcaratum and A.maculatum from this species in Minas Gerais, Brazil.…”
Section: (En Linea Directa News Report April 2007)mentioning
confidence: 99%
“…Smith (1974) recorded A. longirostre in Trinidad from small wild animals. Nava et al (2007b) also indicated the presence of tick A. longirostre in Trinidad. Voltzit (2007) mentioned that in 1955 T.H.G.…”
Section: Amblyomma Humeralementioning
confidence: 90%
“…Everard and Tikasingh (1973) found A. humerale on rodents (Oryzomys capito and Proechimys guyannensis) from Turure Forest, Trinidad. Nava et al (2007b) and Voltzit (2007) also mention the presence of A. humerale in Trinidad. Other observed hosts include birds (Morshed et al 2005), lizards, opossums, anteaters (Labruna et al 2002), and dogs (BarrosBattesti et al 2006).…”
Section: Amblyomma Humeralementioning
confidence: 99%
“…Amblyomma rotundatum Koch, 1844 is a hard-bodied tick (Acari: Ixodida: Ixodidae) that is typically found on amphibians and reptiles. This parthenogenetic tick has a biogeographical range from Argentina to Mexico, including the Caribbean Islands (Jones et al 1972, Guglielmone et al 2003, Nava et al 2007, Voltzit 2007, Guzman-Corejo et al 2011) and southern part of Florida , Corn et al 2011. Zoogeographically, A. rotundatum is now established in localized areas within the southernmost fringe of the Nearctic Region.…”
Section: Introductionmentioning
confidence: 99%